Estado de conservação e aspectos da vegetação de nascentes do riacho Grilo-SE - Santos, Thadeu Ismerim Silva (2009)
This research was developed with the goal to evaluate the river-head of the hydrographic microbasin at Grilo stream, concerning its conservation state, soil usage and surrounding vegetation aspects. Its main target is to support recovery and preservation acts, evolving sources and riparian vegetation. The study has been carried out in the hydrographic microbasin at Grilo stream, which belongs to Piauitinga river hydrographic sub-basin, located at Boquim and Salgado counties, Sergipe. To identify the river-head were used a map from the region and a GPS device, as well a local inhabitant s aid. The river-head characterization was done considering the conservation state (preserved, disturbed or degraded), water source type (punctual or diffuse), soil usage and most prevalent disturbances in the area. Other sorts of information collected were: specific location, property owner s name and geographical coordination. Out of 65 river-head identified at the remarked area, 95,38% are degraded, 3,08% are disturbed and 1,54% preserved. Concerning the type of water source, punctual sources (66,15%) have been identified more frequently than diffuse ones (33,85%). Most registered kinds of disturbances were weed (48,19%), presence of domestic animals (48,83%) and clear cutting of vegetation (44,19%). Most representative soil usages found are livestockfarming (55,81%) and permanent farming (46,51%). Along vegetation screening, some sources have been selected: three of those among punctually degraded (PDe) and diffusely degraded (DDe) categories, and one among diffusely disturbed (DDi) and punctually disturbed (PDi) categories, where 4 plots of 500m² (10x50m) have been distributed, and the individuals at breast height diameter (DAP at 1,30m from the soil surface) ≥ 5,0cm were measured. The parameters evaluated were: density, dominance, frequency, relevance index, Shannon-Weaver s diversity index (H ), Pielou s equability index (J ), and Jaccard s index (Sj) to evaluate forest resemblance among the river-head. As for local forest diversity, sites which are diffusely concerned in general (62) presented more sorts of species than punctually degraded (33), as well as degraded ones (59) own greater diversity than disturbed ones (32). Referring to sucessional state of vegetation, there has been recorded a majority of climax light-demanding species, in every category studied. Relating to forest resemblance, water source sites have been divided in three groups (PDi1/DDi1/DDe1; PDe1/PDe2/PDe3/DDe2 and DDe3). Species diversity and richness reached greater numbers at the diffusely degraded category. As a result of the studies developed at the Grilo stream hydrographic microbasin and its importance to the region, it is notorious that it requires urgent recovery attitudes evolving these river-head sites. As for phytossociological analysis, some species have shown more capacity to adapt to the conditions of the studied environments (dry and flooded areas), an information that should be taken in account when planning river-head and water streams recovery programs.